Electrophysiological dysfunction and cellular disruption of sensory neurones during incubation with Treponema pallidum. Issue 4 (August 1982) - Oakes, S G; Repesh, L A; Pozos, R S; Fitzgerald, T J
Abstract : Treponema pallidum (Nichols strain) was incubated with cultured nerve cells derived from dorsal root ganglia of rat embryos. The electrophysiological response of these neuronal cells was then investigated. Cells exposed to 2 X 10(8) treponemes/ml responded abnormally after 13 hours and failed to respond after 18 hours. In contrast, control preparations exposed to heat-inactivated treponemes or to culture medium responded normally after 72 hours. Extended incubation with viable treponemes resulted in various degrees of nerve cell disruption as shown by scanning electron microscopy. With some cells holes in the cytoplasmic membrane were detected; with others a coagulated matrix of apparent nuclear material and remnants of cytoskeletal elements indicated more severe destruction. These findings may explain the painless nature of many of the clinical manifestations of syphilis as well as the severe damage to central nervous system tissue in tertiary and congenital syphilis.